PENTINGNYA PELATIHAN DAN PENGALAMAN KERJA PADA KARYAWAN CV.BAROKAH TRUUS MANDIRI SINGARAJA - Andini, Disa (LPPM Universitas Buana Perjuangan Karawang, 2023)
This research is a study that aims to determine the importance of training and workexperience in CV. Baroque Truss Mandiri. This research was conducted with qualitativemethods. With data collected through in-depth interviews, observation, anddocumentation studies, data analysis was then carried out using an interactive analysismodel through three stages, namely (1) data reduction, (2) data presentation, (3)drawing conclusions. The results of the study show that training and work experienceare very important for CV companies. Barokah Truus Mandiri where training is neededfor employees who do not have work experience where training is the seed of experience,therefore training and work experience are needed for companies engaged inconstruction and development for the continuity and success of the company